2010
DOI: 10.1007/s00330-010-1891-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumour thickness in oral cancer using an intra-oral ultrasound probe

Abstract: ObjectivesTo investigate tumour-thickness measurement with an intra-operative ultrasound (US) probe.MethodsA retrospective data analysis was undertaken for a total of 65 patients with a T1-2 oral cavity cancer, who were seen at a tertiary referral centre between 2004 and 2010. The correspondence between tumour thickness measured by ultrasonography and histopathology was assessed by Pearson’s correlation coefficient, and also between tumour thickness and the development of neck metastasis.ResultsIn 11 cases, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 32 publications
2
57
1
1
Order By: Relevance
“…It was concluded that for clinically N0 oral cancer, elective neck dissection was indicated in patients with depth invasion of more than 2 mm because in these tumors the risk of metastases reached 40%. 3,18 On the other hand, study did by Fukano et al, showed that tongue tumours exceeding 5 mm carried a risk of 65% for neck metastases, whereas those infiltrating 5 mm or less had a risk of only 6%. 22 Yuen et al, showed in their study that tumour thickness is prognostic for both nodal and local recurrence in oral carcinomas.…”
Section: 17mentioning
confidence: 98%
See 3 more Smart Citations
“…It was concluded that for clinically N0 oral cancer, elective neck dissection was indicated in patients with depth invasion of more than 2 mm because in these tumors the risk of metastases reached 40%. 3,18 On the other hand, study did by Fukano et al, showed that tongue tumours exceeding 5 mm carried a risk of 65% for neck metastases, whereas those infiltrating 5 mm or less had a risk of only 6%. 22 Yuen et al, showed in their study that tumour thickness is prognostic for both nodal and local recurrence in oral carcinomas.…”
Section: 17mentioning
confidence: 98%
“…20 They found this method to be superior to conventional US for this region and more accurate for the estimation of tumour thickness. 3,19 US thus seem to be the optimal technique in patients with no limited mouth opening or base of tongue involvement. US measurement is more reliable than MRI for the measurement of tumour thickness, especially in superficial lesions.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…This has significance for carcinoma in situ, as the risk of microscopic lymph node metastasis increases significantly above 7 mm. 9 Bone invasion of the jaws can be detected, and sonographic appearances distinguishing invasion or remodelling of the palate have been previously described. 10 Here, we described the diagnostic efficacy of ultrasound for pre-biopsy characterization of two cases of minor salivary gland malignancy.…”
Section: Discussionmentioning
confidence: 99%